Emotive Behavior Therapy and Flexibility activities on Pain Level among Breast Cancer Patients - I Gede Sunardianta Sunardianta; Rr. Sri Endang Pujiastuti; Dina Indrati Dyah Sulistyowati (Alta Dharma Publisher, 2021)
Breast cancer is one of the most common non-cutaneous malignancies in women. Breast cancer can cause various problems such as fatigue, pain, fear, depression and even decreased quality of life. Pain is one of the most aggravating symptoms of cancer arising from cancer. Alternative treatment with complementary therapies, namely emotive behavior therapy and flexibility activities which can reduce the pain level of breast cancer patients. This study aims to determine the effect of emotive behavior therapy and flexibility activities on the pain level in breast cancer patients. This study quasi experimental used a non-eqiuvalent pre-test and post-test approach control group design involving 42 breast cancer patients. Selected through technique non probability sampling with purposive sampling method is divided into 2 groups, namely 18 respondents in the intervention group who were given emotive behavior therapy and flexibility activities, while 24 respondents in the control group were only given medical therapy according to hospital standards. Measurement of pain intensity was carried out twice before and after treatment, then the data were analyzed using Paired t test and Independent t test. Independent t test showed significant difference p value of 0.001 (<0.05) that the intervention group very well in reducing pain level compared with the control group. The conclusion, emotive behavior therapy and flexibility activities are very effective in reducing pain level in breast cancer patients.